Степова рослинність Центрального Поділля - Дідух, Я.П.; Вашеняк, Ю.А. (Український ботанічний журнал, 2012)
На основании флористической классификации характеризируется степная растительность
Центрального Подолья. Она представлена 2 порядками, 5 союзами, 13 ассоциациями, 1 субассоциацией, 2 вариантами. Наиболее типичными для региона являются сообщества союзов Fragario viridi-Trifolion montani и Festucion valesiacae (1 субассоциация, 2 варианта описаны впервые). Сообщества союзов Cirsio-Brachypodion pinnati и Artemisio marschalliani-Elytrigion
intermediae фрагментарно представлены на данной территории. Сообщества порядка Stipo
pulcherrimae-Festucetalia pallentis союза Bromo pannonici-Festucion pallentis спорадически распространены в долине реки Днестр. Описана новая ассоциация — Lino hirsuti-Cleystogenetum
bulgarici. Steppe vegetation in Central Podillya, Ukraine, is characterized on the basis of floristic classification.
It is represented by 2 orders, 5 alliances, 13 associations, 1 subassociation, and 2 variants. The
communities of Fragario viridi-Trifolion montani and Festucion valesiacae alliances are typical for the
region (1 subassociation and 2 variants are newly described). The communities of Cirsio-Brachypodion
pinnati and Artemisio marschalliani-Elytrigion intermediae alliances are fragmentarily represented.
The communities of Stipo pulcherrimae-Festucetalia pallentis order of Bromo pannonici-Festucion
pallentis alliance occasionally occur in the valley of the Dnister River. A new Lino hirsuti-Cleystogenetum
association is described.